HLA antibody screening in kidney transplantation: current guidelines - Wettstein, Daniel; Opelz, Gerhard; Süsal, Caner (Langenbeck's archives of surgery, 2014)
In organ transplantation, the introduction of the solid phase immunoassay technology radically changed the practice of antibody monitoring against human leukocyte antigens (HLA).
Published online: 23 November 2013
Gesehen am 19.08.2020